NREL-5MW Wind Turbine Noise Prediction by FWH-LES - Claudio Bernardi; Federico Porcacchia; Claudio Testa; Pietro De Palma; Stefano Leonardi; Stefania Cherubini (International Journal of Turbomachinery, Propulsion and Power, 2023)
This paper deals with large onshore wind turbine aeroacoustics. Noise from the NREL 5 MW device is predicted by the permeable-surface Ffowcs Williams–Hawkings equation (FWH-P), starting from the postprocessing of LES data on different acoustic surfaces <semantics>S</semantics>. Their size and placement is aimed at embedding most of the aerodynamic sources of sound surrounding rotor and nacelle. Due to the presence of eddies that inevitably cross <semantics>S</semantics>, this paper compares results from open and closed acoustic surfaces, and the outflow disk averaging technique. The issues related to the interpolation process of LES data on <semantics>S</semantics> is discussed as well. In order to assess the LES/FWH-P aeroacoustic platform, LES and FWH-P pressures are compared in the very-near field. It is shown that, within the limits of the discretization settings imposed by the interpolation procedure and for the Reynolds number working condition investigated herein, the lack of quadrupole sources outside the permeable surface(s) deeply affect the quality of FWH-P acoustic pressures with respect to direct LES signals.